The scientific production of nature-based tourism: bibliometric analysis of the Clarivate Analytics databases - Rivero Guerra, Aixa O. (Revista General de Información y Documentación, 2021)
In this study the coverage and the main bibliometric research indicators of nature-based tourism are analyzed in the Clarivate Analytics databases (1900-2020). The majority of the scientific production is observed between the years 2010 and 2020 in indexed journals in the main collection of Web of Science, the other databases contribute in limited ways to the publications that are indexed in this platform. Research is focused on ecotourism and rural tourism, published in diverse languages; while the scientific knowledge of adventure, indigenous, responsable, and wildlife tourism are in the initial stages of growth and expansion. Investigations in Economics and Business, Ecology and the Environment, Geography, and Biodiversity and Conservation are preferred by researchers. The scientific community has demonstrated a marked interest in indexed journals, which accumulate a higher number of citations than books or conference communications. The majority of the open access journals are in the consolidation phase and are gaining popularity in the scientific field, between 55,23% (SJR) and 77,32% (JCR) are not yet found in an impact index. Europe is the leader in this sector, while Latin America and Africa demonstrate incipient scientific development with the exception of Brazil, Mexico and South Africa. Journals with restricted access, principally those indexed in Q1, are the most productive, count on the highest number of contributing authors, with a higher balance of accumulated citations, a higher average of citations per year and a higher h-index in comparison with open access journals.